Zbirka nalog iz Matematičnih metod II z rešitvami - Žulj, Maja (University of Maribor Press, 2017)
Mathematical methods II - Exercises with solutions. This teaching resource comprises exercises for students who need to gain knowledge of the subject Matematične metode II. The exercise order is the same as in the textbook named Matematične metode II, therefore, before we give exercises we always specify the name of chapter of the textbook mentioned above to which the exercises relate (Differential equations, Functions of several variables, Straight lines and planes in space, Vector analysis, Trigonometric series, Probability theory and Linear programming). In order to understand the subject matter, it is necessary to know the basics that were given in the course of Matematične metode I and in the same named textbook. At the end of each chapter there are solutions to all exercises of the chapter. The solutions of first several exercises are written with all middle steps and needed theory, so, also students who are new to the subject can follow the steps an solve the exercises successfully.